2003
DOI: 10.1093/humrep/deg004
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary report on nitric oxide-mediated oxidative damage in adolescent varicocele

Abstract: In adolescents with a varicocele, there is an increase in nitrotyrosine concentration within the spermatic vein that can cause protein nitration and cytotoxicity via its reaction with various molecular targets. This could have repercussions on both sperm and testis function. We conclude that an oxidative stress status is present and should be considered as an indication for varicocele treatment in the adolescent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 34 publications
4
49
1
Order By: Relevance
“…In accordance with our observation, Vossen and De Smet (2015) (Vossen and De Smet, 2015) have shown that antioxidants can be used as therapy to decrease nitrite toxicity (AlGayyar et al, 2014;Al-Gayyar et al, 2016). Interestingly, NO has been connected to an elevation in lipid peroxidation and MDA in both humans (Romeo et al, 2003) and experimental rats (Özdamar et al, 2004). A rise in NO following eNOS overexpression has been connected to germ cell apoptosis in a cryptorchidism germ mouse model (i.e.…”
Section: Discussionsupporting
confidence: 82%
“…In accordance with our observation, Vossen and De Smet (2015) (Vossen and De Smet, 2015) have shown that antioxidants can be used as therapy to decrease nitrite toxicity (AlGayyar et al, 2014;Al-Gayyar et al, 2016). Interestingly, NO has been connected to an elevation in lipid peroxidation and MDA in both humans (Romeo et al, 2003) and experimental rats (Özdamar et al, 2004). A rise in NO following eNOS overexpression has been connected to germ cell apoptosis in a cryptorchidism germ mouse model (i.e.…”
Section: Discussionsupporting
confidence: 82%
“…Venous stasis-induced hypoxia, iNOS up-regulation, malondialdehyde (MDA), and nitric oxide (NO) generation in the varicocelized testes have been previously reported [Romeo et al 2003;Turkyilmaz et al 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species/reactive nitrogen species (ROS/RNS) seem to be involved in the oxidative damage in these pathologies (Peltola et al 1995, Romeo et al 2003. In experimental models, heat stress of testis and testicular cells has been associated with spermatocyte apoptosis (Yin et al 1997, Ikeda et al 1999, Lue et al 1999, Rockett et al 2001, Somwaru et al 2004) and ROS formation (Ikeda et al 1999, Ishii et al 2005, with a likely activation of the intrinsic pathway of apoptosis ; see Moreno et al (2012) for a review).…”
Section: Introductionmentioning
confidence: 99%